Intramedullary spinal cord metastasis from primary esophageal carcinoma. (3rd June 2015) - Dalkilic, T; Tymchak, Z; Kindrachuk, M; Fourney, D
Abstract : Background: Intramedullary spinal cord metastasis (ISCM) are rare with primary lung, breast and melanoma accounting for up to 80% of cases. Diagnosis is often delayed or incorrect and these lesions can often be mistaken for primary astrocytoma or ependymoma given similar radiologic features. Methods: We present the case of an 80 year-old male with rapidly progressive quadriparesis and an enhancing intramedullary lesion at C4-7 with diffuse peri-lesional edema. The patient had previously undergone resection of non-metastatic esophageal carcinoma. Results: Bone scan revealed no evidence of skeletal or organ metastases. The patient underwent C5-7 laminectomy and resection of tumor with intra-operative monitoring. Final pathology revealed metastatic adenocarcinoma consistent with esophageal primary. PETCT revealed recurrent esophageal disease and pleural-based metastatic deposits. The patient went on to receive palliative radiotherapy to the cervicothoracic spine. Neurologic status improved marginally. Conclusions: ISCM from primary esophageal carcinoma is extremely rare. We present to our knowledge one of three reports of such in the literature. Hematogenous dissemination via Batson's plexus and peri-veretebral plexuses is thought to be the likely route of spread. Treatment is primarily palliative, however surgical resection should be considered in the absence of metastatic disease.